Micellar high performance liquid chromatographic determination of Itraconazole in bulk, pharmaceutical dosage forms and human plasma - Rizk, Mohamed; Toubar, Safaa Shafik; El-Alamin, Maha Mahmoud Abou; Azab, Marwa Mohamed Mahmoud (European Journal of Chemistry, 2014)
A micellar liquid chromatographic method was developed for determination of Itraconazole in bulk, dosage form and human plasma using µBondapack cyano column and a mobile phase consisting of 0.1 M sodium dodecyl sulphate, 20% 1-propanol, 0.3% triethylamine in 0.02 M orthophosphoric acid (pH = 3.5). The UV detection was achieved at 258 nm. Various chromatographic parameters were studied, e.g. types of columns, pH of mobile phase, concentration of sodium dodecyl sulphate, 1-propanol, triethylamine, etc .The method was linear over the concentration range 16.4-320.0 µg/mL with regression coefficient 0.999 and limit of detection 5.4 µg/mL in bulk. Inter and intra-day results showed %RSD < 1.49%. The result obtained by the proposed method was compared with that obtained by the reference HPLC technique. Furthermore, the proposed method was successfully applied as stability-indicating method for determination of Itraconazole under different stressed conditions. The method showed good selectivity, repeatability, linearity and sensitivity according to the evaluation of the validation parameters.